PENGARUH PENGETAHUAN PRODUK, LABEL ORGANIK KOMUNITAS, DAN PERILAKU PENCARIAN INFORMASI TERHADAP MINAT BELI PRODUK ORGANIK DI KOMUNITAS ORGANIK INDONESIA - Lestari, Goldie Shaumy; Sadeli, Agriani Hermita; Pardian, Pandi; Fatimah, Sri (Universitas Galuh Ciamis, 2021)
Environmental and food security issues has caused organic farming practice to grow globally, including in Indonesia. One of the problems in Indonesia’s organic farming is the cost of organic certification as well as it’s long process. As a solution to this problem, Komunitas Organik Indonesia took an initiative to form a curration program called White Flower Label to guarantee that their member’s products are indeed organic. This study uses quantitative design and a survey method using questionnaire. The sample size used was 30 respondents. The technique used is explanatory, to explain how product knowledge (X1), community-assessed organic label (X2), and information seeking behaviour (X3) influence purchase intention (Y). The results shows that only information seeking behaviour (X3) has a significant effect on purchase intention, while product knowledge (X1) and community-assessed organic label doesn’t have any significant effect.